2019
DOI: 10.1093/eurheartj/ehz120
|View full text |Cite
|
Sign up to set email alerts
|

Early goal-directed haemodynamic optimization of cerebral oxygenation in comatose survivors after cardiac arrest: the Neuroprotect post-cardiac arrest trial

Abstract: Aims During the first 6–12 h of intensive care unit (ICU) stay, post-cardiac arrest (CA) patients treated with a mean arterial pressure (MAP) 65 mmHg target experience a drop of the cerebral oxygenation that may cause additional cerebral damage. Therefore, we investigated whether an early goal directed haemodynamic optimization strategy (EGDHO) (MAP 85–100 mmHg, SVO2 65–75%) is safe and could improve cerebral oxygenation, reduce anoxic brain damage, and improve outcome when compared with a MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
133
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 28 publications
2
133
1
2
Order By: Relevance
“…The current analysis found the proportion of using vasopressors is higher among non-survivors, which is consistent with the findings of previous observational studies (20,22,25). Although previous studies have shown an association between higher MAP goals achieved with vasopressors and improved outcomes (21,24), a high dosage of vasopressors could cause complications, such as arrhythmia and decreased peripheral perfusion (26). We also found the proportion of using hypothermia is higher among non-survivors, which might not have clinical significance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current analysis found the proportion of using vasopressors is higher among non-survivors, which is consistent with the findings of previous observational studies (20,22,25). Although previous studies have shown an association between higher MAP goals achieved with vasopressors and improved outcomes (21,24), a high dosage of vasopressors could cause complications, such as arrhythmia and decreased peripheral perfusion (26). We also found the proportion of using hypothermia is higher among non-survivors, which might not have clinical significance.…”
Section: Discussionsupporting
confidence: 88%
“…Laurikkala et al prospectively found an association between unfavorable neurological outcome and time spent below a MAP of 70 mmHg in the first 48 h after ROSC, but did not find an association between high vasopressor load and poor outcome(23). In 2019, the Neuro-protect post-CA trial, compared the current standard of care (MAP 65mmHg) with a goal-directed hemodynamic optimization strategy (MAP 85-100mmHg, SVO2 65-75%) found targeting a higher MAP improved brain oxygenation but did not improve the neurological outcome(24).…”
mentioning
confidence: 99%
“…Jakkula et al [6] reported that early higher achieved MAP did not affect the serum concentration of neuronspeci c enolase, S100B protein, cardiac troponin, regional frontal cerebral oxygenation, and epileptic activity on the electroencephalography. Ameloot et al [16] did not nd the bene ts of a higher MAP target assessed by magnetic resonance imaging of the cerebrum. Compared with the standard MAP regimen, targeting high MAP in the rst hours of an experimental ECPR model did not result in any hemodynamic improvement nor in a decrease in the amount of infused uid.…”
Section: Discussionmentioning
confidence: 95%
“…Für den septischen Schock konnten bereits randomisierte Studiendaten erhoben werden, die zeigen, dass durch eine Anhebung auf hochnormale Werte (MAP 80-85 mmHg) kein Vorteil zu verzeichnen ist [33]. Bei Patienten nach kardiopulmonaler Reanimation gibt es allerdings Hinweise in einer kleinen randomisierten Studie, dass die zerebrale Oxygenierung verbessert werden könnte [34]. Ob diese Beobachtung allerdings auch Unterschiede im klinischen Überleben mit adäquater zerebraler Funktion bewirken könnte, muss erst durch adäquate, multizentrische Studien geklärt werden.…”
Section: Caveunclassified